2016
DOI: 10.14202/vetworld.2016.856-861
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary-adrenocortical adjustments to transport stress in horses with previous different handling and transport conditions

Abstract: Aim:The changes of the hypothalamic pituitary adrenal (HPA) axis response to a long distance transportation results in increase of adrenocorticotropic hormone (ACTH) and cortisol levels. The purpose of the study was to quantify the level of short-term road transport stress on circulating ACTH and cortisol concentrations, related to the effect of previous handling and transport experience of horses.Materials and Methods:The study was performed on 56 healthy horses after short-term road transport of 30 km. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
(26 reference statements)
1
20
0
1
Order By: Relevance
“…CORT is susceptible to be modified by the manipulation of stressful and painful stimuli, circadian rhythm, exercise, transport, hypoglycemia and stress [26][27][28][29]. Therefore, establishing a reference interval for the basal CORT is difficult.…”
Section: Reference Values For Cortisol Levelsmentioning
confidence: 99%
“…CORT is susceptible to be modified by the manipulation of stressful and painful stimuli, circadian rhythm, exercise, transport, hypoglycemia and stress [26][27][28][29]. Therefore, establishing a reference interval for the basal CORT is difficult.…”
Section: Reference Values For Cortisol Levelsmentioning
confidence: 99%
“…B. Transport (13,36), bei systemischen und schmerzhaften Erkrankungen (25,29,45) und bei sportlichen Leistungsanforderungen (11,21,24,35,37,45). Beim Quarter Horse im Training konnte ein linearer Zusammenhang zwischen dem Anstieg der Kortisolkonzentration…”
Section: Herz-und Atemfrequenz Sowie Innere Körpertemperatur In Relatunclassified
“…Transportation is associated with factors that may contribute to gastric ulceration such as physiologic stress responses (increased heart rate and serum cortisol concentrations), changes in feeding practices and water consumption, and changes in GI microbiota . Our study was conducted to determine the impact of 12 hours of transportation without food or water on gastric ulcer scores and gastric fluid (GF) pH in horses.…”
Section: Introductionmentioning
confidence: 99%
“…Transportation has been suggested as a risk factor for gastric ulceration 13 and a recent survey of transport-associated health problems indicated that gastrointestinal (GI) problems occur frequently in association with transportation of horses. 14 Transportation is associated with factors that may contribute to gastric ulceration such as physiologic stress responses (increased heart rate and serum cortisol concentrations), [15][16][17][18][19][20][21] changes in feeding practices and water consumption, 22,23 and changes in GI microbiota. 12,24 Our study was conducted to determine the impact of 12 hours of transportation without food or water on gastric ulcer scores and gastric fluid (GF) pH in horses.…”
Section: Introductionmentioning
confidence: 99%